Penatalaksanaan Fisioterapi Pada Kondisi Pasca Operasi Fraktur Colles Dextra Di Rsud Dr Harjdono Ponorogo - Milanti, Milanti; , Yulisna Mutia Sari SST. Ft, MSc (GRS) (2016)
Background: Colles fracture is transverse fracture of the distal radial shaft with dorsal angulation of the distal fragment. Objective: To determine the modalilities of physiotherapy with infra red and therapy exercise to decrease pain, increase ROM and increase muscle strength in the case of colles fracture dextra. Result: After therapy as much as six times in getting the result to the reduction of tenderness of T1 : 3,8 be T6 : 2,1 and the motion of the pain T1 : 4,1 be T6 : 2,3, an increase in range of motion active dextra wrist in the sagital and frontal T1 = S : 15°-0°-15° be T6 = S : 20°-0°-20° and T1 = F : 5°-0°-5° be T6 = F : 10°-0°-10°, whereas ROM passive dextra wrist in the sagital and frontal also increase the T1 = S : 20°-0°-15° be T6 = S : 25°-0°-20° and T1 = F : 5°-0°-10 be T6 = F : 10°-0°-10° and as well as an increase in muscle strength in dorsal flexion movement of T1 : 2+ be T6: 3-, palmar flexion of T1 : 2+ be T6 : 3-, while radial deviation and ulnar deviation there has not been an increase muscle strength. Conclusions: infrared can reduce pain because of they give the effect of relaxation on the condition of post colles fracture dextra, and therapeutic exercise can increase the strength muscle and improve the range of motion (ROM) on condition post colles fracture dextra.